Kesadaran Intensionalitas dalam Fenomenologi Edmund Husserl: Suatu Studi Epistemologi dalam Upaya Perbandingan dengan Metode Ilmiah: Intentionality Awareness in Edmund Husserl’s Phenomenology: An Epistemological Study in Comparative Perspective with the Scientific Method - Hafidz Hasyim (Fenomena, 2009)
The crisis of Western epistemology, dominated by positivism and psychologism, has reduced consciousness to mere empirical facts and created a subject-object dichotomy that fails to grasp the essence of knowledge. This study critically examines Edmund Husserl’s phenomenology, particularly his concept of intentionality, as a foundational epistemological alternative. The research aims to describe and analyze the historical emergence of Husserl’s thought, the originality of his concept of intentionality, and its implications for reconstructing epistemological foundations. Using a qualitative library research method with historical, hermeneutical, and deductive-inductive approaches, this study systematically analyzes Husserl’s primary texts. The findings reveal that intentionality—consciousness always being conscious of something—serves as the basic structure of knowledge, enabling a return to the things themselves (zu den Sachen selbst) through phenomenological reduction (epoche). This method overcomes the limitations of both rationalism and empiricism by establishing an a priori relationship between subject and object. The study concludes that Husserl’s intentionality offers a new paradigm for epistemology, recovering the substance of historical experience and reconstructing the essence and structure of knowledge, while recommending further application of this method in contemporary social sciences. Krisis epistemologi Barat yang didominasi positivisme dan psikologisme telah mereduksi kesadaran menjadi fakta empiris semata serta menciptakan dikotomi subjek-objek yang gagal menangkap esensi pengetahuan. Penelitian ini mengkaji secara kritis fenomenologi Edmund Husserl, khususnya konsep intensionalitasnya, sebagai alternatif epistemologis yang fundamental. Penelitian ini bertujuan mendeskripsikan dan menganalisis kemunculan historis pemikiran Husserl, orisinalitas intensionalitas, serta implikasinya bagi rekonstruksi fondasi epistemologi. Dengan metode penelitian kepustakaan kualitatif serta pendekatan historis, hermeneutik, dan deduktif-induktif, penelitian ini menganalisis secara sistematis teks-teks utama Husserl. Temuan penelitian menunjukkan bahwa intensionalitas—kesadaran selalu sadar akan sesuatu—merupakan struktur dasar pengetahuan yang memungkinkan kembalinya kepada hal itu sendiri (zu den Sachen selbst) melalui reduksi fenomenologis (epoche). Metode ini mengatasi keterbatasan rasionalisme dan empirisme dengan membangun relasi apriori antara subjek dan objek. Penelitian menyimpulkan bahwa intensionalitas Husserl menawarkan paradigma baru bagi epistemologi, memulihkan substansi pengalaman historis, serta merekonstruksi esensi dan struktur pengetahuan, dengan rekomendasi penerapan metode ini lebih lanjut dalam ilmu-ilmu sosial kontemporer.